2010
DOI: 10.5964/ejop.v6i2.186
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of students’ psychosocial well-being and their measurement: Validation of a students’ Psychosocial Well Being Inventory

Abstract: This paper presents findings from a validation study of a measurement instrument for the dimensions of students' psychosocial well-being. Researches to date suggest many separate but related dimensions of psychosocial well-being. In the current study, psychosocial well-being is considered to have four dimensions: subjective well-being related to every day's events, subjective well-being related to faculty events, psychological well-being and social well-being. Diener's (1985) and Seligman's (2002) models of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 47 publications
1
23
0
6
Order By: Relevance
“…Conversely, a low score shows that the respondent struggles to feel comfortable with that particular concept. Ryff's Psychological Well-being Inventory subscales yield acceptable to excellent internal consistency(Negovan, 2010). Cronbach's alpha for the overall scale and the subscales ranged from .72 to .85.…”
mentioning
confidence: 95%
“…Conversely, a low score shows that the respondent struggles to feel comfortable with that particular concept. Ryff's Psychological Well-being Inventory subscales yield acceptable to excellent internal consistency(Negovan, 2010). Cronbach's alpha for the overall scale and the subscales ranged from .72 to .85.…”
mentioning
confidence: 95%
“…Studies that investigated psychological well-being as a single-factor dimension also evidenced the positive relationship between this and PGI (Kashubeck-West & Meyer, 2008;Lasun & Odufowokan, 2012;Negovan, 2010;Robitschek, 1999;Shorey et al, 2007) Higher levels of PGI were associated with the presence of higher indices of emotional well-being, social well-being (Negovan, 2010) 2009; Stevic & Ward, 2008); positive mental health (Ogunyemi & Mabekoje, 2007;Vaingankar et al, 2011); and positive affect (Hardin et al, 2007;Robitschek & Keyes, 2009). Consequently, people who had higher levels of PGI were more likely to possess lower levels of negative affect (Hardin et al, 2007), stress (Hardin et al, 2007;Shorey et al, 2007), lower levels of perceived stigma (Sultan, 2011) and more chance of healthily recovering from traumatic experiences (Borja & Callahan, 2009;Callahan et al, 2013).…”
Section: Personal Growth Initiative and Relationships With External Vmentioning
confidence: 99%
“…In addition, earlier work among student samples from Romanian public universities showed scores above the midpoint of the response scale when using the SWLS (Negovan, 2010). Further cross-country analyses on life satisfaction among Romanians in Romania and Greeks in Greece (Stefenel, 2012), revealed that Romanian registered higher scores than Greeks but significantly lower than the scores of Romanians in our study.…”
Section: Discussionmentioning
confidence: 59%